The Effects of Dantrolene on Prostaglandin-Induced Contraction of Myometrium isolated From Ovariectomised Rat - Konar, Vahit (Fırat University, 2001)
Objective: Dantrolen inhibits calcium-induced calcium release from ryanodine sensitive intracellular stores. The aim of this study was to investigate the effects of dantrolene on prostaglandin F2α stimulated myometrial contractions in vitro. Material and method: Myometrial strips were removed from adult non-pregnant Wistar rats following decapitation and suspended in an organ bath containing Krebs' solution at 37°C and pH 7.4, constantly gassed with 95% oxygen-5% carbon dioxide mixture and isometric contractions were recorded. Results: Dantrolene dose dependently and reversibly inhibited contractions induced by PGF2α (1mM) induced contractions. Conclusion: In conclusion, calcium-induced calcium release from ryanodine sensitive intracellular stores is thought to play important roles in PGF2α stimulated contractions of isolated rat myometriyum.

Amaç: Dantrolen riyanodine duyarlı hücre içi kalsiyum depolarından kalsiyum salıverilmesini bloklar. Bu çalışmanın amacı dantrolenin prostaglandin F2α ile uyarılan miyometriyum kontraksiyonları üzerine in vitro etkilerini incelemektir. Gereç ve yöntem: Miyometriyal şeritler yetişkin, gebe olmayan ovariyektomize edilmiş Wistar sıçanlarından dekapitasyondan sonra alınarak içerisinde pH'sı 7.4 olan 370C'de Krebs solüsyonu bulunan ve %95 oksijen-%5 karbondioksit karışımı ile sürekli gazlandırılan organ banyosunda asılarak izometrik kontraksiyonlar kayıt edildi. Bulgular: Dantrolen uygulaması doz bağımlı ve geri dönüşümlü olarak prostaglandin F2α (PGF2α, 1µ M) ile indüklenen kontraksiyonları inhibe etti. Sonuç: Sonuç olarak, riyanodin duyarlı kalsiyum depolarından kalsiyum salıverilmesi sıçan izole miyometriyumunda PGF2α ile uyarılan kasılmalarda rol oynayan önemli bir mekanizma olduğu sanılmaktadır.
OVARİYEKTOMİZE SIÇANDAN İZOLE EDİLMİŞ MİYOMETRİYUMDA PROSTAGLANDİNLE İNDÜKLELEN KONTRAKSİYONLAR ÜZERİNE DANTROLENİN ETKİLERİ